The letter to the Ephesians - Cohick, Lynn H. (New International Commentary on the New Testament (NICNT), 2020)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Excursuses -- General Editor's Preface -- Author's Preface -- Abbreviations -- Bibliography -- Introduction -- I. Authorship -- A. Authorship Question Unpacked -- B. Ephesians as Deutero-Pauline -- 1. Theology -- 2. Literary Style -- 3. Historical Circumstances -- 4. Relationship between Ephesians and Colossians -- C. Pseudepigraphy in the Ancient World -- D. Genuine or Forgery -- E. Secretaries and Letter Writing in the Ancient World -- F. Conclusions on the Pseudepigraphic Paul and Ephesians -- II. Recipients -- A. Textual Evidence for the Omission of "in Ephesus" -- B. Evaluation of the Evidence -- III. Occasion for Writing Ephesians -- IV. Purpose of Ephesians -- V. First-Century Ephesus -- A. Cult of Artemis -- B. Imperial Cult -- C. Magic and Powers in Ephesus -- D. Judaism in Ephesus -- E. Ephesus and Paul's Visit (Acts 19) -- VI. Date and Provenance of Ephesians -- A. Ephesus -- B. Rome -- VII. Structure of Ephesians -- A. Analysis of Letter -- B. Outline of Letter -- VIII. Outline of the Commentary -- IX. Theology of Ephesians -- A. Paul's Use of the Old Testament -- B. Christology or Theology? -- C. God the Father -- D. God the Spirit -- E. The Lord Jesus Christ -- 1. Jesus Christ as Son of the Father -- 2. Christ -- 3. Lord -- 4. Christ Our Peace -- F. Trinitarian Language in Ephesians -- G. The Church in Ephesians -- H. Mystery of the Gospel and the Church -- X. The New Perspective on Paul and Ephesians -- Text and Commentary -- I. Paul's Opening Greeting (1:1-2) -- II. Theological Explication of the Gospel (1:3-3:21) -- A. Eulogy and Prayer (1:3-23) -- 1. Thanksgiving to God through Christ (1:3-14) -- Thematic Outline of 1:3-14 -- a. Adopted by the Father (1:3-6) -- b. Redeemed by the Son (1:7-12) -- c. Sealed by the Holy Spirit (1:13-14).